Penerapan Model Trait Treatment Interaction Berbantuan Aplikasi Ispring Suite untuk Mempengaruhi Literasi Sains di SMAN 16 Padang - Rahmadani, Nudiya; aswirna, prima; Ramadhan, Syahrul; Amalina, Amalina (Natural Science: Jurnal Penelitian Bidang IPA dan Pendidikan IPA, 2019)
Research on the Implementation of Trait Treatment Interaction Model Assisted by Ispring Suite Application to Influence Science Literacy at SMAN 16 Padang. This research is a quasi-experimental study with the research design used is the Randomized Control Group Only Design. The study population was all students of class XI MIA Academic Year 2018/2019. The sample technique in this study is Clauster Random Sampling and the research sample is class XI MIA 2 as an experimental class (High class) and class XI MIA 3 as a control class (Slow class). The final test to study physics is given in both sample classes of essay questions. The data analysis technique used to test hypotheses is the Paired Sample T-Test, provided that the data are normally distributed and the data groups have homogeneous variances. The results of statistical analysis showed that the average value of physics learning outcomes of experimental class students was 81.47 while in the control class 79.44. The results of the Paired Sample T-Test analysis were of significance 0.001 <0.05. Based on the results of the study it can be concluded outside the reception area of H0. Thus H0 is rejected and H1 is accepted, then T count 45.768> T table 0.67874 then there are differences in students who have the ability to quickly (faster learner) by using self-learning (self learning) is higher than regular learning (regular teaching) with additional learning ( tutorial) to influence Science Literacy.